A theological turn in Edith Stein’s phenomenology? - D´ıaz Medina, C´esar Samir (2023)
The present work intends to show that Edith Stein’s phenomenological position, in On the problem of empathy and in Introduction to philosophy, can characterize her philosophy as carrier of the germ of a ”theological turn”, from the early phenomenological era. We consider three key points to signal this turn. These are the ideas of i) original consciousness and passivity, ii) the limit of human knowledge, and iii) empathy towards God. In the treatment of these ideas, we can appreciate how Edith Stein’s phenomenology makes its way towards a certain transcendence, hence the encounter with theology is natural, or that there are theological developments of phenomenology.